BETWEEN AVATARS AND ALGORITHMS: GOVERNING PARALLEL UNIVERSES IN THE AGE OF THE METAVERSE - Cavalcante, Ailton Ferreira (Seven Editora, 2026)
This article examines the metaverse as a new architecture of social reality in which immersive digital environments governed by algorithms and artificial intelligence increasingly structure identity, value, power, and experience. Rather than approaching the metaverse as a speculative future technology, the study analyzes it as a set of sociotechnical architectures already in operation, as evidenced by algorithmic video platforms, generative AI, synthetic advertising, and identity simulation systems. Drawing on simulation theory, philosophy of information, and the political economy of data, the article argues that these environments produce a code-based ontology in which reality is computationally constructed rather than merely represented. The study introduces the theory of consciousness protection as a normative framework to address the cognitive, emotional, and decisional risks associated with the algorithmic colonization of human experience. Finally, the GIS Cycle (Governance, Innovation, and Sustainability) is applied as an analytical matrix to assess the institutional legitimacy, ethical responsibility, and social sustainability of metaverse governance.